The Effects of Cooperative Teaching Method Used in Badminton Teaching on Physical Fitness in Student Ningbo University of Finance & Economics - Wu, Xiaoli; Promthep, Kreeta; Hengsoko, Ekasak (วารสารนวัตกรรมการศึกษาและการวิจัย, 2026)
This study aimed to apply the cooperative teaching method in badminton courses through a teaching experiment. The objectives of the research were: (1) To compare the differences in physical fitness within the experimental and control groups before and after the intervention. 2) To compare the differences in physical fitness between the experimental group and the control group after the intervention. Eighty first-year students from Ningbo University of Finance and Economics participated; they were all avid badminton players without any prior professional experience. They were naturally split into two groups, Group A and Group B, with no discernible differences in their physical fitness or interest in sports. The participants were chosen from elective public courses. Numerous techniques were used in the study, such as expert interviews, experimental design, literature review, and mathematical statistical analysis. The learning effects and physical fitness outcomes (i.e., agility, endurance, explosive strength, and speed) of the two groups were compared before and after the 12-week intervention using independent samples t-tests and paired samples t-tests. The research results were found as follows; In the within-group comparison, both the experimental group and the control group have achieved more significant physical fitness after the experiment, and the achievements of the experimental group are more significant than those of the control group. In the between-group comparison, the differences in physical fitness between the experimental group and the control group are more significant, with the experimental group showing better performance than the control group. The results support the effectiveness of the cooperative teaching method in improving physical fitness in badminton instruction.